Fast redigeringsskjema for verb? Semantikk versus grammatikalisering - Grønvik, Oddrun (Nordiske Studier i Leksikografi, 2007)
The purpose of this article is to clear the ground for a general and common editorial schema for lexicographic treatment of all verbs in the Norwegian language. Therefore, claims that verbs should be classified into groups with special qualities and functions are examined. In grammatical tradition, verbs are content words, excepting several small subsets of verbs used in constructing multi-word verb forms, which according to the grammars require different treatment. In Norwegian lexicograhy another classification has emerged, counterpoising ”big verbs” with multiple functions and a multitude of derived phrasal verbs against the rest. These classifications are examined against the defining practice shown in entries on individual verbs, and a general maximum model for ordering and defining verbs, including derived phrasal verbs, is presented.